Seamless Virtual Service: - Kaufmann, Karen F.; Miller, Claire A. (Qualitative and Quantitative Methods in Libraries, 2020)
Abstract:   The impact of the coronavirus, also known as COVID-19, on higher education and more specifically on academic libraries across the globe has been an experience that is unprecedented in this 21 st century. Though pandemics certainly have their historical impact documented in literature, this article speaks to the response of an academic library to the impact of this virus that has rocked the world in the spring of 2020.  Specifically, this article presents how a Florida State College managed and marketed this pivotal event to deliver library services, resources, and instruction seamlessly in the virtual environment. Seminole State College (SSC) l ibrary’s response to the unfolding COVID-19 campus shutdown highlights the importance of flexible and iterative planning, cooperative and collaborative problem solving, and librarian ownership and investment in providing excellent student services in a time of unprecedented disruption. This case study examines the six-week period of rapid transition from a traditional physical academic library with a hybrid approach to instruction and service to a one hundred percent online library in response to social distancing guidelines and campus closures.   SSC l ibraries proactively planned for a campus shut down for a week before the college officially closed. This “just in case” planning was essential in the process of training staff in new tasks, assessing and assigning resources and tasks, and developing new resources to meet possible demands. Persistent communication with students, faculty and the college community were key elements in the decisions and strategies implemented by librarians and library staff. Sustaining the holistic delivery of the academic library in a fully online environment became the driving focus for the pivot from on-campus interactions. When the college did close, faculty librarians used the one-week shutdown of campus and classes to develop and deploy new solutions in staffing, resources, and workflows to support students in this online format.  Librarians took ownership of the library’s services and resources while using an existing suite of online tools in new ways to serve students. The approach of “no one has told us ‘no’ yet” allowed the team of librarians to think outside the existing college structures and protocols. While transitioning at speed was a difficult process, the collaborative and cooperative librarian ownership-based approach was essential to continuing to provide the best possible service to our students in a time of crisis.